EVALUASI PELAKSANAAN LAYANAN DASAR BIDANG PRIBADI-SOSIAL DI SMP NEGERI 1 YOGYAKARTA - Barida, Muya (JURNAL FOKUS KONSELING, 2016)
Program implementation is very influential toward service outcome. This study aims to know the similarities or the differences between planning and implementation program by counselor. This study refers to discrepancy model which consist of four stages : (1) design, (2) installation, (3) process, and (4) product. The research subject is counselor of state junior high school 1 Yogyakarta. The result of questionnaire and interview shows that the score is relatively high. In conslusion, there are similarities between planning and implementation program of basic counseling.Keywords: evaluation, basic counseling of individual-social field.